Genetic advantage and Equality of Opportunity in education: Two definitions and an empirical application - Rita Dias Pereira (Tinbergen Institute, 2021)
The literature of Equality of Opportunity (EOp) has long acknowledged the existence of 'talents', 'innate ability' or 'genetic ability'. Nonetheless, attempts to explicitly incorporate a measure of innate ability in the quantification of EOp have been rare. On the other hand, the literature of social-science genetics has found credible genetic-based components of EOp, without an explicit quantification of overall EOp. In addition, there exists prevalent disagreement within both kinds of literature on whether innate ability should be perceived as a fair or unfair source of advantage. This paper proposes to quantify EOp while explicitly including a genetic-based measure of innate ability. It proposes two formal definitions of EOp that draw on both stances regarding the compensation of innate ability. Novel testable implications are derived. The educational attainment polygenic index is used as a measure of innate ability while correcting for genetic nurture and accounting for the correlation between genes and other circumstances. An empirical application in the US Health and Retirement Study finds that the share of inequality of opportunity is 26% under the view that genetic differences are unfair sources of advantage and 21% otherwise. A comparative analysis over cohorts reveals that the trend in EOp depends on the definition adopted; if genetic advantage is a fair source of inequality then EOp has improved; the opposite holds if one considers genetic advantage an unfair source of inequality. These results highlight the importance of accounting for genetic differences in the EOp framework.
Keywords: 330; Equality of Opportunity; Education; Childhood Social Class; Genes; Luck